MODEL KEPEMIMPINAN ENTREPRENEURSHIP DALAM PENDIDIKAN TEKNOLOGI DAN KEJURUAN UNTUK MENINGKATKAN KEMANDIRIAN LULUSAN SMK - Jiorgi, Thomas; Nenden Azka Zakhiha; Ganefri; Elizon; Adrian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The transformation of the world of work in the era of Industry 4.0 and Society 5.0 has shifted the orientation of technological and vocational education from merely producing skilled workers to developing graduates who are adaptive, innovative, and capable of creating employment opportunities independently. However, the high unemployment rate among Vocational High School (SMK) graduates indicates that vocational education still faces challenges in fostering graduates’ economic independence. Therefore, a leadership approach is required that not only focuses on educational management but also promotes a sustainable entrepreneurial culture within schools. This study aims to analyze the concept of entrepreneurial leadership in technological and vocational education and to formulate a leadership model capable of enhancing the independence of vocational high school graduates. This study employed a Systematic Literature Review (SLR) method by analyzing relevant national and international scientific articles published between 2022 and 2026. The review process was conducted systematically through the identification, selection, evaluation, and synthesis of literature discussing entrepreneurial leadership, teaching factory, project entrepreneurship, industry partnerships, entrepreneurial mindset, and vocational education. The findings indicate that entrepreneurial leadership is a strategic approach that integrates innovation, creativity, risk-taking, opportunity recognition, and industry collaboration into the management of vocational education. The study reveals that the success of entrepreneurship development in vocational schools is strongly influenced by the principal’s ability to establish a culture of innovation, develop business-oriented teaching factories, strengthen partnerships with business and industry sectors, and implement project-based entrepreneurship learning. Furthermore, direct interaction between students and business environments has been shown to enhance motivation, self-confidence, decision-making skills, creativity, and entrepreneurial competencies required to cope with the dynamic changes of the labor market. Based on the synthesis of the literature, this study proposes a novel framework, namely the Integrated Entrepreneurial Leadership Model for Vocational Education, which integrates three key components teaching factory, industry partnerships, and project entrepreneurship within a sustainable school entrepreneurial ecosystem. This study contributes conceptually to the development of vocational education management by positioning school principals as entrepreneurial leaders who act as innovators, collaborators, and drivers of educational transformation. The implications of the study suggest that the implementation of entrepreneurial leadership can strengthen the relevance of vocational education to future industrial demands, enhance students’ entrepreneurial readiness, and promote the development of vocational school graduates who are more independent, adaptive, competitive, and globally competitive.